Meditation-Based Therapy for Chronic Low Back Pain Management: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Lin, Ting-Han; Tam, Ka-Wai; Yang, Yu-Ling; Liou, Tsan-Hon; Hsu, Tzu-Herng; Rau, Chi-Lun (Pain medicine (Malden, Mass.), 2022)
Abstract Background Chronic low back pain (CLBP) is among the most common types of pain in adults. Currently, injections and analgesic and nonsteroidal anti-inflammatory drugs are often provided for patients with CLBP. However, their effectiveness remains questionable, and the safest approach to CLBP remains debated. Meditation-based therapies constitute an alternative treatment with high potential for widespread availability. We evaluated the applicability of meditation-based therapies for CLBP management. Methods We performed a systematic review and meta-analysis of randomized controlled trials to evaluate the efficacy of meditation-based therapies for CLBP management. The primary outcomes were pain intensity, quality of life, and pain-related disability; the secondary outcomes were the experienced distress or anxiety and pain bothersomeness in the patients. The PubMed, Embase, and Cochrane databases were searched for studies published from the databases’ inception dates until July 2021, without language restrictions. Results We reviewed 12 randomized controlled trials with 1,153 patients. In 10 trials, meditation-based therapies significantly reduced the CLBP pain intensity compared with nonmeditation therapies (standardized mean difference [SMD] −0.27, 95% confidence interval [CI] = −0.43 to −0.12, P = 0.0006). In seven trials, meditation-based therapies also significantly reduced CLBP bothersomeness compared with nonmeditation therapies (SMD −0.21, 95% CI = −0.34 to −0.08, P = 0.002). In three trials, meditation-based therapies significantly improved patient quality of life compared with nonmeditation therapies (SMD 0.27, 95% CI = 0.17 to 0.37, P < 0.00001). Conclusions In conclusion, meditation-based therapies constitute a safe and effective alternative approach to CLBP management.